2023
DOI: 10.3390/jcm12134175
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Distribution of Brimonidine and Brinzolamide after Topical Instillation of a 0.1% Brimonidine Tartrate and 1% Brinzolamide Fixed-Combination Ophthalmic Suspension: An Interventional Study

Abstract: Purpose: To evaluate the concentrations of brimonidine and brinzolamide in the vitreous and aqueous humor after instillation of a 0.1% brimonidine tartrate and 1% brinzolamide fixed-combination ophthalmic suspension. Methods: The present investigation involved patients with macular holes or idiopathic epiretinal membranes who were planning to undergo vitrectomy. One week prior to surgery, the patients received twice-daily topical treatment with 0.1% brimonidine tartrate and 1% brinzolamide fixed-combination op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This post hoc pooled analysis integrated and reanalyzed data sourced from three clinical studies that determined brimonidine concentrations in the aqueous and vitreous humor after the topical application of the following eye drops containing brimonidine: 0.1% brimonidine tartrate ophthalmic solution (Aiphagan Ò ; Senju Pharmaceutical Co., Ltd., Osaka, Japan), 0.1% brimonidine tartrate and 0.5% timolol (equivalent to 0.68% timolol maleate) fixedcombination ophthalmic solution (Aibeta Ò ; Senju Pharmaceutical Co., Ltd.) and 0.1% brimonidine tartrate and 1% brinzolamide fixed-combination suspension (Ailamide Ò ; Senju Pharmaceutical Co., Ltd.) [8][9][10] (Tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This post hoc pooled analysis integrated and reanalyzed data sourced from three clinical studies that determined brimonidine concentrations in the aqueous and vitreous humor after the topical application of the following eye drops containing brimonidine: 0.1% brimonidine tartrate ophthalmic solution (Aiphagan Ò ; Senju Pharmaceutical Co., Ltd., Osaka, Japan), 0.1% brimonidine tartrate and 0.5% timolol (equivalent to 0.68% timolol maleate) fixedcombination ophthalmic solution (Aibeta Ò ; Senju Pharmaceutical Co., Ltd.) and 0.1% brimonidine tartrate and 1% brinzolamide fixed-combination suspension (Ailamide Ò ; Senju Pharmaceutical Co., Ltd.) [8][9][10] (Tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…No correlation was found among brimonidine, timolol or brinzolamide concentrations in the aqueous and vitreous humor and corneal thickness, corneal endothelial cell density, tear secretion (Schirmer's test), eye axial length, height or BMI (Figs. 5,6,7,8,9,10).…”
Section: Effects Of Other Factorsmentioning
confidence: 99%
“…While α2 agonists have been reported to cause vasoconstriction in some capillaries [46][47][48], they have been shown to cause vasodilation in other, larger vessels [47,49,50]. In the eye, it has been reported that BBFC eye drops reach the vitreous body and retinal vessels [51]. When the vitreous concentration of brimonidine surpasses the threshold for α2 adrenergic receptor activation [52], the expression of endothelial nitric oxide synthase (eNOS) increases, inducing NO, which has a vasodilating effect on the vasculature, including in the retinal vessels [53].…”
Section: Plos Onementioning
confidence: 99%